2015
DOI: 10.1002/2014jd021817
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of modeled microwave land surface emissivities with satellite‐based estimates

Abstract: An accurate estimate of the microwave surface emissivity is necessary for the retrieval of atmospheric quantities from microwave imagers or sounders. The objective of this study is to evaluate the microwave land surface emissivity modeling of the Community Radiative Transfer Model (CRTM), providing quantitative statistic information for further model improvements. First, the model‐simulated emissivity is compared to emissivity estimates derived from satellite observations (TELSEM, Tool to Estimate Land Surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 30 publications
1
21
0
Order By: Relevance
“…Enhancement of land and ocean surface emissivity/radar cross-section retrievals (e.g. Ferraro et al, 2013;Tian et al, 2013;Turk et al, 2014;Prigent et al, 2015;Harrison et al, 2016) is important because these are vital environmental conditions required by the precipitation retrieval algorithms, especially as the algorithms move toward more physically based descriptions of surface properties (e.g. Kummerow et al, 2015).…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%
“…Enhancement of land and ocean surface emissivity/radar cross-section retrievals (e.g. Ferraro et al, 2013;Tian et al, 2013;Turk et al, 2014;Prigent et al, 2015;Harrison et al, 2016) is important because these are vital environmental conditions required by the precipitation retrieval algorithms, especially as the algorithms move toward more physically based descriptions of surface properties (e.g. Kummerow et al, 2015).…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%
“…It is worth noting the many existing evaluation studies using the out-of-the-box models-models with the default parameter values. These include, for example, Ferraro et al [2013], Ringerud et al [2014], and Prigent et al [2015]. The current study takes advantage of the recent work of Harrison et al [2015] to include the same models but with calibrated parameters.…”
Section: Methods 1 (Phys)mentioning
confidence: 99%
“…The study found considerable differences not only between the modeled and retrieved emissivities but also among the retrieved emissivity values from different sensors or different data providers. Follow-up studies have been expended to include other surface types [Tian et al, 2013], more reliable retrieved emissivity retrievals [Ringerud et al, 2014], or broader spatial and temporal coverages [Norouzi et al, 2015;Prigent et al, 2015].…”
Section: Introductionmentioning
confidence: 99%
“…The advantage of using emissivity instead of brightness temperatures is that emissivity estimates are free from atmospheric effects such as from clouds and aerosols, and they are sensitive to soil characteristics [ Prigent et al, ; Norouzi et al, ; Tian et al, ; Prakash et al, ]. Many studies have also confirmed that land emissivity estimates are very important for accurate precipitation retrieval, snowpack detection, land surface process studies, and numerical model data assimilation [ Tian and Peters‐Lidard , ; AghaKouchak et al, ; Ferraro et al, ; Shahroudi and Rossow , ; Prigent et al, ; Prakash et al, ; Turk et al, ]. Since the transition between freeze and thaw states generally depends on the dielectric changes of soil and vegetation types, the use of land emissivity estimates for FT detection is expected to be more accurate since brightness temperature observations contain atmospheric and temperature effects.…”
Section: Introductionmentioning
confidence: 99%